SPEAKING ACTIVITIES IN YOUNG LEARNERS CLASSROOM: THE IMPLEMENTATION OF PROJECT-BASED LEARNING APPROACH - Susi Fitria (Journal of English and Education, 2013)
This paper reports on a study aiming at investigating the variety of speaking activities conducted by an English teacher of a private elementary school. The data were taken from observations, structured interviews, and documents examination. To analyze the data, Brown’s (2004) six categories of classroom speaking performances were used. The findings reveal that there were 11 kinds of speaking activities conducted by the teacher within 5 meetings, namely: drilling, directed response, sentence/dialogue completion, picture-cued, translation (of limited stretches of discourse), question and answer, discussion, games, oral presentation, retelling a story, and singing a song. This result shows that PBL approach encourages teachers to provide more varied speaking activities for the students. Keywords:   Young learners, elementary school, speaking activities, project-based learning approach